PEMBELAJARAN MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI MADRASAH IBTIDAIYAH NEGERI (MIN) BAWAN KECAMATAN AMPEK NAGARI KABUPATEN AGAM - Nurhasanah; M. Yemmardhotillah (El-Rusyd, 2020)
Problems in this study that teachers SKI simply knowing the nature of the child while in the classroom , while outside the classroom do not know anymore , in the learning process teachers are required to have skills in carrying out the lessons to be performing well , in order to reach the desired goal . On the other hand , when the learning took place , seen a lot of students who play around while learning , as if they were bored with the material presented by the teacher . This study aims to determine the teacher preparation SKI before making the learning process at MIN Bawan District of Ampek Nagari Agam district , steps in the implementation of the teaching and learning process SKI in MIN Bawan District of Ampek Nagari Agam and techniques of learning evaluation SKI in MIN Bawan District of Ampek Nagari Agam . So hopefully with this research study subjects SKI rise in Bawan MIN Agam Kecamatan Ampek Nagari.